Who Knows Best what the People Want: Women or Men?: A Study of Political Representation in India - Karl-Oskar Lindgren, Magdalena Inkinen and Sten Widmalm (Comparative Political Studies 2009; 42; 31, 2009)
The notion of representation lies at the heart of liberal democratic thinking, and over the years considerable effort has gone into defining and measuring the concept. The least common denominator in the voluminous literature is that in a representative political system there should be a certain amount of attitudinal congruence between masses and elites. One much-debated strategy for obtaining a better match between elite and mass policy opinion is that of increasing the representation of women in important decision-making positions in society. Using data on nearly 5,000 elite-mass dyads within 24 Indian villages, the authors find strong support for the view that a more equal representation of women increases opinion congruence between masses andelites. The results are challenging because they show that women are not only better equipped than men to politically represent women but also that they are better at representing men-and the results are shown to apply in a variety of socioeconomic contexts